Organic acid composition and consumer acceptability of fermented fish produced from black tilapia (Oreochromis mossambicus) and Javanese carp (Puntius gonionotus) using natural and acid-assisted fermentation - Mohamad Azman, Ezzat; Mohd Ghazali, Hasanah; Karim, Roselina; Zare, Davood (Rynnye Lyan Resources, 2021)
Ikan pekasam is an example of traditional fermented food products in Malaysia, prepared from freshwater fish such as black tilapia (Oreochromis mossambicus) and Javanese carp (Puntius gonionotus), salt and ground roasted rice, which is added as the only source of carbohydrate. However, some producers add tamarind (Tamarindus indica) pulp and/or dried slices of Garcinia atroviridis to assist the fermentation process. In this study, there was no correlation detected between pH value, titratable acidity (% lactic acid), salt concentration, organic acid composition and the consumer acceptability of ikan pekasam commercial samples made of black tilapia as well as Javanese carp. The organic acid composition in both natural and acid-assisted fermented ikan pekasam from black tilapia and Javanese carp were compared. The results obtained showed that lactic acid was the major organic acid detected, followed by succinic acid and acetic acid. The addition of tartaric and/or garcinia acids was proven to reduce the fermentation time. Therefore, the addition of acid has assisted the fermentation process by increasing the total organic acid content, mainly lactic acid. Moreover, the 9-point hedonic scale showed that ikan pekasam made of Javanese carp had higher overall acceptability due to tender flesh/muscle texture compared to black tilapia regardless of the fermentation process and organic acid content.